Citizen Science as an Ecosystem of Engagement: Implications for Learning and Broadening Participation. (22nd June 2022) - Allf, Bradley C; Cooper, Caren B; Larson, Lincoln R; Dunn, Robert R; Futch, Sara E; Sharova, Maria; CAVALIER, Darlene
Abstract: The bulk of research on citizen science participants is project centric, based on an assumption that volunteers experience a single project. Contrary to this assumption, survey responses ( n = 3894) and digital trace data ( n = 3649) from volunteers, who collectively engaged in 1126 unique projects, revealed that multiproject participation was the norm. Only 23% of volunteers were singletons (who participated in only one project). The remaining multiproject participants were split evenly between discipline specialists (39%) and discipline spanners (38% joined projects with different disciplinary topics) and unevenly between mode specialists (52%) and mode spanners (25% participated in online and offline projects). Public engagement was narrow: The multiproject participants were eight times more likely to be White and five times more likely to hold advanced degrees than the general population. We propose a volunteer-centric framework that explores how the dynamic accumulation of experiences in a project ecosystem can support broad learning objectives and inclusive citizen science.